Comparison of Ergonomic Assessment Results in the Automotive Polymer Industry: Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) and Rapid Upper Limb Assessment (RULA) Methods - Khadijah Sayyidatun Nisa; Abdussalam Topandi; Isma Wulansari; Fauziah Aulia; Bismo Zulfikar Mustofa (LPPM Politeknik Aceh Selatan, 2024)
Musculoskeletal disorders (MSDs) encompass injuries to muscles, nerves, joints, and connective tissues, affecting the neck, back, and limbs. The polymer automotive industry, particularly in manufacturing automotive components using plastic injection tools, involves workers with diverse postures. Non-ergonomic postures can lead to muscle tension and health issues, emphasizing the importance of safety and ergonomics. This study employs the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) and Rapid Upper Limb Assessment (RULA) methods to assess working postures. In the production sector, the average RULA score is 3.8 (31.67%), indicating moderate risk and suggesting further investigation. Conversely, the non-production sector's average RULA score is 3.4 (28.33%), indicating a lower risk but still necessitating changes. CMDQ analysis on 12 respondents reveals posture variation. In the production sector, the average CMDQ score is 2.5 (20.83%), signaling moderate risk and advocating for further investigation. This study lays groundwork for downstream polymer industries to enhance efficiency, quality, and safety.